2016
DOI: 10.1113/jp272489
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cdk5 function in the nucleus accumbens decreases wheel running and may mediate age‐related declines in voluntary physical activity

Abstract: Key pointsr Physical inactivity, which drastically increases with advancing age, is associated with numerous chronic diseases.r The nucleus accumbens (the pleasure and reward 'hub' in the brain) influences wheel running behaviour in rodents.r RNA-sequencing and subsequent bioinformatics analysis led us to hypothesize a potential relationship between the regulation of dendritic spine density, the molecules involved in synaptic transmission, and age-related reductions in wheel running. Upon completion of follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 85 publications
2
9
0
Order By: Relevance
“…These observations suggest that the specific increase in thin spines observed in this study could result from the time when the VWR mice were euthanized, that is, during the light phase when mice are resting (i.e., voluntary short-term withdrawal from VWR). Similar to our observations in mice, a recent study in female Wistar rats demonstrated that 3 weeks of VWR is associated with increased total spine density, and a relative increase and decrease in thin and stubby spines, respectively [61]. Collectively, these studies provide strong rationale to investigate how VWR alters synaptic maturation and function in the NAc, and to identify the functional consequences of altered VWR-associated NAc MSN spine formation on stress resilience.…”
Section: Discussionsupporting
confidence: 87%
“…These observations suggest that the specific increase in thin spines observed in this study could result from the time when the VWR mice were euthanized, that is, during the light phase when mice are resting (i.e., voluntary short-term withdrawal from VWR). Similar to our observations in mice, a recent study in female Wistar rats demonstrated that 3 weeks of VWR is associated with increased total spine density, and a relative increase and decrease in thin and stubby spines, respectively [61]. Collectively, these studies provide strong rationale to investigate how VWR alters synaptic maturation and function in the NAc, and to identify the functional consequences of altered VWR-associated NAc MSN spine formation on stress resilience.…”
Section: Discussionsupporting
confidence: 87%
“…The intensity of absolute nucleus accumbens responsiveness may be lower in this age group. Recent studies in older animals have shown changes in nucleus accumbens functioning and behavior ( Ruegsegger et al., 2017 ). However, the small sample size may have limited the statistical power to detect a smaller effect size.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF induces local synaptic plasticity [ 82 ] and more interestingly cyclin-dependent kinase 5 (Cdk5), a serine/threonine kinase involved in the rescue of synaptic plasticity [ 83 ], is involved in the BDNF-stimulated dendritic growth in hippocampus [ 84 ]. In poststroke patients, the role of Cdk5 has been associated with the long-term postischemic neurodegeneration and Cdk5 might be a pharmacological target; its inhibition or gene silencing increases the expression of BDNF in the hippocampal neurons [ 85 ]. The loss of this serine/threonine kinase in the nucleus accumbens reduces the ability to sustain a muscular physical exercise [ 85 ].…”
Section: Bone-skeletal Muscle Biomarkers In Strokementioning
confidence: 99%
“…In poststroke patients, the role of Cdk5 has been associated with the long-term postischemic neurodegeneration and Cdk5 might be a pharmacological target; its inhibition or gene silencing increases the expression of BDNF in the hippocampal neurons [ 85 ]. The loss of this serine/threonine kinase in the nucleus accumbens reduces the ability to sustain a muscular physical exercise [ 85 ]. The relationship between the different degrees of the muscular activity (training, sustained and endurance physical exercise, moderate aerobic exercise, etc.)…”
Section: Bone-skeletal Muscle Biomarkers In Strokementioning
confidence: 99%